Data sharing for zoonoses surveillance in Senegal: challenges and opportunities - Diouf, Khady; Bordier, Marion; Caffin, Jean Hugues; Fall, Assane Gueye; Bakhoum, Mame Thierno; Omoijade Irabor, Thomas-Julian; Antoine-Moussiaux, Nicolas; Bada-Alambedji, Rianatou (Frontiers in Veterinary Science, 2026)
IntroductionZoonoses are a growing threat to global health, requiring effective integrated surveillance. Such surveillance relies on the structured and secure sharing of data between human, animal and environmental health stakeholders. In Senegal, despite advances in the One Health approach, surveillance data sharing remains limited. This study aims to analyze challenges related to surveillance data sharing in Senegal and identify ways to improve the situation.MethodsThis study adopted an inductive qualitative approach to explore the challenges and opportunities of data sharing through 61 semi-structured interviews with three categories of key stakeholders: (i) system managers, (ii) initiative holders, and (iii) community actors. A thematic analysis was applied to the participants’ discourse to identify the main issues and opportunities for improvement. Data were triangulated by cross-referencing interview contents with institutional documents and previous studies to ensure the robustness of the results.ResultsThree significant challenges are holding back data sharing for zoonosis surveillance: (i) limited technical and organizational capacities, which compromise interoperability, accessibility, and data utilization; (ii) contrasting attitudes among stakeholders, between motivation and mistrust or reluctance, linked to transparency and recognition concerns; and (iii) fragmented governance, characterized by the absence of a clear regulatory framework, a lack of coordination, and insufficient sustainable funding. However, opportunities exist, including stakeholder motivation when collaboration is recognized and rewarding, and existing institutional frameworks that could be strengthened.ConclusionTo advance data sharing and strengthen zoonotic surveillance in Senegal, the study highlights the necessity to harmonize existing surveillance systems, reinforce capacities, and establish collaborative governance. These efforts should address stakeholders’ concerns while supporting their motivation to contribute to an integrated surveillance system.